A Dissertation Report Topology Optimization of Aircraft Wing Components Using Optistruct - RAJESH A (2008)
INTERNAL GUIDE : Shri ArokkiSwamy EXTERNAL GUIDE: Satish Chandra USN NO : 1MJ07MAE12 CARRIED OUT AT : Council Of Scientific and Industrial Research National Aerospace Laboratories Bangalore-560017 ACC NO : AE01
Keywords: Aircraft Wing Components